Early Life Displacement Due to Armed Conflict and Violence, Early Nutrition, and Older Adult Hypertension, Diabetes, and Obesity in the Middle-Income Country of Colombia (2019)
Objective: We examine the importance of early life displacement and nutrition on hypertension (HTN) and diabetes in older Colombian adults (60+ years) exposed to rapid demographic, epidemiological, and nutritional transitions, and armed conflict. We compare early life nutritional status and adult health in other middle- and high-income countries. Method: In Colombia (Survey of Health, Wellbeing and Aging [SABE]-Bogotá), we estimate the effects of early life conditions (displacement due to armed conflict and violence, hunger, low height, and not born in the capital city) and obesity on adult health; we compare the effects of low height on adult health in Mexico, South Africa (Study on Global Ageing and Adult Health [SAGE]), the United States, and England (Health and Retirement Study [HRS], English Longitudinal Study of Ageing [ELSA]). Results: Early life displacement, early poor nutrition, and adult obesity increase the risk of HTN and diabetes in Colombia. Being short is most detrimental for HTN in Colombian males. Discussion: Colombian data provide new evidence into how early life conditions and adult obesity contribute to older adult health. © The Author(s) 2018.